(untitled) (Indian Journal of Chemistry (IJC), 2024)
A set of twelve new quinazoline arylidene/heteroarylidene motifs were synthesized by forming Schiff bases from the 3-amino-8-methyl-2-(p-tolyl)quinazolin-4(3H)-one intermediate. These compounds were analyzed and tested for their anti-inflammatory and antimicrobial potential. The in-vitro results for anti-inflammatory activity showed that compound 6g (2-Br) exhibited the most potential with an inhibition of 96.89±0.83 against the standard medication. Compound 6d (4-OH) had the second-highest anti-inflammatory inhibition of 92.64±0.38. In terms of antimicrobial activity, compound 6d showed the highest inhibitory impact ranging from 12.5 to 50 μg/ml against specific bacterial and fungal pathogens. Compound 6g also demonstrated good action against E. coli, Klebsiella sp., B. megaterium, S. aureus, and A. niger species. Compounds 6e, 6j, and 6k had strong antibacterial activity but only modest antifungal efficacy in antimicrobial activity tests. According to the SAR study, compounds 6d, 6e, and 6k that have EDGs such as hydroxyl at the ortho, meta, and para positions have both potent antimicrobial and anti-inflammatory activities. Moreover, compounds 6c, 6g, and 6j which have EWGs (-Cl, -Br, and -NO2) in the ortho and para positions exhibit better anti-inflammatory activity as compared to the meta-derivative 6b. Further evaluation of compounds 6d and 6g with standard antibiotics is crucial for treating harmful microorganisms.